Dietary factors during pregnancy and atopic outcomes in childhood: A systematic review from the European Academy of Allergy and Clinical Immunology. Issue 8 (6th August 2020) - Venter, Carina; Agostoni, Carlo; Arshad, S. Hasan; Ben‐Abdallah, Miriam; Du Toit, George; Fleischer, David M.; Greenhawt, Matthew; Glueck, Deborah H.; Groetch, Marion; Lunjani, Nonhlanhla; Maslin, Kate; Maiorella, Alexander; et al.
Abstract: Rationale: Allergic diseases are an increasing public health concern, and early life environment is critical to immune development. Maternal diet during pregnancy has been linked to offspring allergy risk. In turn, maternal diet is a potentially modifiable factor, which could be targeted as an allergy prevention strategy. In this systematic review, we focused on non‐allergen‐specific modifying factors of the maternal diet in pregnancy on allergy outcomes in their offspring. Methods: We undertook a systematic review of studies investigating the association between maternal diet during pregnancy and allergic outcomes (asthma/wheeze, hay fever/allergic rhinitis/seasonal allergies, eczema/atopic dermatitis (AD), food allergies, and allergic sensitization) in offspring. Studies evaluating the effect of food allergen intake were excluded. We searched three bibliographic databases (MEDLINE, EMBASE, and Web of Science) through February 26, 2019. Evidence was critically appraised using modified versions of the Cochrane Collaboration Risk of Bias tool for intervention trials and the National Institute for Clinical Excellence methodological checklist for cohort and case‐control studies and meta‐analysis performed from RCTs. Results: We identified 95 papers: 17 RCTs and 78 observational (case‐control, cross‐sectional, and cohort) studies. Observational studies varied in design and dietary intakes and often had contradictory findings. Based on our meta‐analysis, RCTs showed that vitamin D supplementation (OR: 0.72; 95% CI: 0.56‐0.92) is associated with a reduced risk of wheeze/asthma. A positive trend for omega‐3 fatty acids was observed for asthma/wheeze, but this did not reach statistical significance (OR: 0.70; 95% CI: 0.45‐1.08). Omega‐3 supplementation was also associated with a non‐significant decreased risk of allergic rhinitis (OR: 0.76; 95% CI: 0.56‐1.04). Neither vitamin D nor omega‐3 fatty acids were associated with an altered risk of AD or food allergy. Conclusions: Prenatal supplementation with vitamin D may have beneficial effects for prevention of asthma. Additional nutritional factors seem to be required for modulating the risk of skin and gastrointestinal outcomes. We found no consistent evidence regarding other dietary factors, perhaps due to differences in study design and host features that were not considered. While confirmatory studies are required, there is also a need for performing RCTs beyond single nutrients/foods. Abstract : Our systematic review focused on the maternal diet in pregnancy and allergy outcomes in the offspring. Results from the observational studies provided no conclusive evidence on whether the mother's diet when pregnant affects the development of offspring allergic disease. Data from the randomized controlled trials indicated that vitamin D supplementation in doses higher than recommended by most countries, lead to a 30% reduction in offspring asthma. As a result, no recommendations about what pregnant women should eat or which supplements to take, to prevent their offspring from developing allergic disease can be made at this stage. Further studies should be performed, using standardised methods focusing on the total diet rather than one nutrient, using validated instruments to measure dietary intake and clearly defining the phenotype ad genetic characteristics of each woman.